2016
DOI: 10.1080/13561820.2016.1227963
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional immersion: Use of interprofessional education collaborative competencies in side-by-side training of family medicine, pharmacy, nursing, and counselling psychology trainees

Abstract: While supported by the Affordable Care Act, in the United States, interprofessional training often takes place after healthcare providers graduate and are practicing in the field. This article describes the implementation and evaluation of an interprofessional training for graduate-level healthcare trainees. A group of interprofessional healthcare faculty provided a weeklong interprofessional immersion for doctoral-level healthcare trainees (n = 24) in Pharmacy, Counselling Psychology, Nursing, and Family Medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 27 publications
1
23
0
2
Order By: Relevance
“…(22) It is also highlighted that IPE on the care of individuals with chronic diseases, like diabetes, where physiopathological knowledge is transversal in medicine and nursing, permits development of clinical skills. (24) From the perspective of bioethics in the practice of health sciences, diverse studies found (25)(26)(27) managed to support that under IPE development is achieved of this vision of ethics and values in students added to the practice and interdisciplinary teamwork. Thereby, it is recognized that at curricular level the programs of health sciences have tried to wage on IPE as a way of enhancing professional collaboration, identifying the role to perform, and developing transversal values for the care of patients, in addition to the joint commitment to maintain knowledge updated to benefit the users, that is, application of evidence-based practice but interprofessional.…”
Section: Contributions Foundmentioning
confidence: 99%
“…(22) It is also highlighted that IPE on the care of individuals with chronic diseases, like diabetes, where physiopathological knowledge is transversal in medicine and nursing, permits development of clinical skills. (24) From the perspective of bioethics in the practice of health sciences, diverse studies found (25)(26)(27) managed to support that under IPE development is achieved of this vision of ethics and values in students added to the practice and interdisciplinary teamwork. Thereby, it is recognized that at curricular level the programs of health sciences have tried to wage on IPE as a way of enhancing professional collaboration, identifying the role to perform, and developing transversal values for the care of patients, in addition to the joint commitment to maintain knowledge updated to benefit the users, that is, application of evidence-based practice but interprofessional.…”
Section: Contributions Foundmentioning
confidence: 99%
“…Penelitian serupa juga menyatakan bahwa terdapat dampak pelatihan interprofesional terhadap pembelajaran yang dirasakan mahasiswa dan perubahan sikap dalam rangkaian eksperimental (Cooper et al 2005, Lindqvist et al, 2005. Sedangkan penelitian yang dilakukan Wlliams et al, Interprofessional immersion training (Boland et al, 2016), sebuah studi dengan tipe interprofessional course (Hylin et al, 2007), dan 1 penelitian menggunakan…”
Section: Pendahuluanunclassified
“…Terdapat (Hagemeier et al, 2014;Watters et al, 2017;Holthaus et al, 2013;Brock et al, 2013;Boland et al, 2016;Hylin et al, 2007;Oza et al, 2015;Schaik, et al 2011). Hanya satu studi menunjukkan tidak ada peningkatan yang signifikan self-efficacy dalam interprofessional training (Williams et al, 2017 Hal tersebut sejalan dengan penelitian (Boland et al, 2016;Tofil et al, 2014;Holthaus, et al 2015) (Hagemeier et al, 2014;Watters, et al, 2017 ;Tofil et al, 2014;Holthaus, et al 2015).…”
Section: Instrumentunclassified
“…4 As a result, interprofessional training in colleges and schools of pharmacy has flourished in the US and internationally. [43][44][45][46][47][48][49] Descriptions of courses on care transitions are emerging, and studies of pharmacist involvement at care transitions have shown improvements in patient care parameters and opportunities for clinical collaboration. [50][51][52] High-fidelity simulation is a practical and highly effective approach to teach skills in interprofessional collaboration.…”
Section: Team-based Competenciesmentioning
confidence: 99%